Model Aplikasi Point of Sale Berbasis Mobile dengan Modul Pre Order Real Time - Alfian Setya Dwi Saputra; Yuli Asriningtias (STMIK Banjarbaru, 2025)
Point of sale (POS) systems are critical to retail operations because they serve as the hub for transaction capture, inventory synchronization, and real time reporting, thereby reducing input errors and accelerating service. This study develops a mobile based point of sale application equipped with a real time pre order mechanism to address issues such as manual transaction recording, delayed recap processes, and limited visibility of scheduled orders. Development followed the Waterfall methodology, comprising the Communication, Planning, Modeling, Construction, and Deployment phases. The proposed architecture is mobile first, providing real time synchronization of stock and order status along with a sales-summary dashboard. System testing employed black box methods on core scenarios, including authentication, master data management, transactions and payments, order scheduling, and reporting. The result is a mobile software solution that implements POS and pre order concepts and has been deployed at ALVIN’S Bakery.Keywords: Point of Sale; Mobile Application; Pre Order; Real Time; Waterfall AbstrakPoint of sale (POS) system penting bagi bisnis ritel karena menjadi pusat pencatatan transaksi, sinkronisasi stok, dan pelaporan real time yang menekan kesalahan input serta mempercepat layanan. Penelitian ini mengembangkan aplikasi point of sale berbasis mobile yang dilengkapi mekanisme pre order real time untuk mengatasi masalah seperti pencatatan transaksi manual, keterlambatan rekapitulasi, keterbatasan visibilitas pesanan yang dijadwalkan. Metode pengembangan aplikasi menggunakan Waterfall system meliputi: communication, planning, modeling, construction, dan deployment. Arsitektur yang diusulkan bersifat mobile first dengan sinkronisasi stok dan status pesanan secara real time serta dashboard ringkasan penjualan. Pengujian sistem menggunakan black box pada skenario inti, mencakup autentikasi, pengelolaan master data, transaksi dan pembayaran, penjadwalan pesanan, serta pelaporan. Hasil penelitian adalah perangkat lunak berbasis mobile dengan penerapan konsep POS dan pre order yang diterapkan pada salah satu bisnis ALVIN’S Bakery.